CULTIVATION OF OYSTER MUSHROOM ( YSTER MUSHROOM (PLEUROTUS FLORIDA) ON PADDY STRAW BY DELAYED SPAWN INOCULATION - R. RAKESH REDDY; R. SOMASHEKHAR; A. B. VEDAMURTHY (The Bioscan, 2010)
The mushroom cultivation is a profitable agri-business and oyster mushroom (Pleurotus florida) is an edible mushroom having excellent flavor and taste. The present work deals with cultivation of Pleurotus ostreatus by standard protocol and delayed spawn inoculation on paddy straw. The result depicts, oyster mushroom on paddy straw by the delayed spawn inoculation is performing better in number of days taken for spawn running, number of days taken for formation of pinheads, number of days taken for formation of fruiting bodies and average number of fruiting bodies over standard protocol of cultivation. The findings are most promiscuous in terms of various parameters including biomass.